PENGUATAN MINAT MEMBACA MELALUI GERAKAN “KACAKARYA” (KAMI MEMBACA KAMI BERKARYA) KELAS IV DI SDN PADARINCANG 1 - Farida, Ida (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the implementation and impact of the Kacakarya Movement (Kami Membaca Kami Berkarya – We Read, We Create) in enhancing reading literacy culture among fourth-grade students at SDN Padarincang 1. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data sources included the school principal, teachers, students, and supporting documents. The results indicate that Kacakarya activities are systematically and participatively designed through school deliberations involving multiple stakeholders. Reading materials are selected according to students’ proficiency levels and managed via an organized borrowing system. In addition to reading, students are encouraged to write summaries and produce creative works, such as poems and stories. The program effectively increases students’ reading interest, comprehension, and self-confidence. Positive outcomes also include higher library visit frequency, active parental involvement, and the creation of a more conducive and inspiring learning environment. Supported by literacy facilities and proactive homeroom teachers, Kacakarya proves effective in fostering sustainable literacy habits. The findings may serve as a reference for other schools seeking to develop contextual and integrated literacy programs, promoting both academic and creative growth.